Photo-excited charge carriers suppress sub-terahertz phonon mode in silicon at room temperature - Bolin Liao (Nature Portfolio, 2016)
Direct measurement of electron-phonon interactions at the single-mode level has been a challenge. Here, Liaoet al. use a three-pulse photoacoustic spectroscopy technique to investigate the damping of a single sub-terahertz coherent phonon mode by photo-excited free charge carriers in silicon at room temperature.